Technological Utopianism and the Idea of Justice - Sand, Martin; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
In this fascinating book, Martin Sand argues that futuristic visions of technological utopias can radically alter our perspective on the world, ourselves, and the role of justice in human life. Throughout the book, Sand convincingly argues that technological utopias can inspire new conceptions of justice and forcefully responds to many anti-utopian arguments. A must-read for anybody interested in the controversial topic of technological utopias! - Sven Nyholm, Professor of the Ethics of Artificial Intelligence at LMU Munich. This open access book advances a modest defence of technological utopias. While technological utopianism is not devoid of risks and elitism, their benefits should not be discounted in an overall assessment. Rather than rejecting them based on a too narrow definition of utopianism, we must acknowledge their potential to exceed the individualist vs. collectivist dichotomy ascribed to traditional utopias. The author argues with reference to Rawls idea of the basic structure that technological utopias challenge our understanding of the scope and location of justice and, thereby, advance the idea of justice. The book critically reviews the most recent literature in political philosophy, where utopias are understood as ideal theories of justice and sides with recent contributions to Utopian Studies, where utopias potential to estrange from the present and galvanize action are underscored. Martin Sand is an Assistant Professor of Ethics and Philosophy of Technology at TU Delft and a Board Member of the Delft Young Academy. He was a member of the theme group on Accountable and Explainable Medical AI at the Netherlands Institute for Advanced Study (NIAS), Amsterdam. Before, he undertook a two-year Marie Skłodowska-Curie-Fellowship project on Moral Luck in Science and Innovation.
Chapter 1. Why utopia instead of what utopia -- Chapter 2. Perfectionism, stagnation and transcendental theorizing -- Chapter 3. Technological anti-anti-utopianism -- Chapter 4. How to and where to justice -- Chapter 5. Justice in technological utopia -- Chapter 6. Conclusions.
Keywords: Science -- Social aspects; Science -- Philosophy; Technology -- Philosophy; Science and Technology Studies; Philosophy of Science; Philosophy of Technology